Criminally ignorant : why the law pretends we know what we don't - Sarch, Alexander (Oxford University Press, 2019)
The willful ignorance doctrine says defendants should sometimes be treated as if they know what they don't. This book provides a careful defense of this method of imputing mental states. Though the doctrine is only partly justified and requires reform, it also demonstrates that the criminal law needs more legal fictions of this kind. The resulting theory of when and why the criminal law can pretend we know what we don't has far-reaching implications for legal practice and reveals a pressing need for change.